2022
DOI: 10.1093/nop/npac021
|View full text |Cite
|
Sign up to set email alerts
|

[18F]-fluoromisonidazole (FMISO) PET/MRI hypoxic fraction distinguishes neuroinflammatory pseudoprogression from recurrent glioblastoma in patients treated with pembrolizumab

Abstract: Response assessment after immunotherapy remains a major challenge in glioblastoma due to an expected increased incidence of pseudoprogression. Gadolinium enhanced magnetic resonance imaging is the standard for monitoring therapeutic response, however, is markedly limited in characterizing pseudoprogression. Given that hypoxia is an important defining feature of glioblastoma regrowth, we hypothesized that [ 18F]-fluoromisonidazole FMISO PET could provide an additional physiological measure for the diagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Regarding the direction and prospect of future investigation, first, the diagnostic value of non- 18 F-FET radiotracers need to be proved in additional cohorts. Second, only a few preliminary studies have shown that the highest diagnostic accuracy would be achieved from the combination of advanced multiparameter MRI and PET imaging ( 9 , 12 , 34 , 36 , 64 ), and therefore future research should focus on the development and validation of such bimodal or multimodal diagnostic models ( 65 ). In addition, the kinetic parameters of dynamic PET imaging have demonstrated excellent performance in glioma grading ( 66 ) and prognosis evaluation ( 16 , 35 , 38 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the direction and prospect of future investigation, first, the diagnostic value of non- 18 F-FET radiotracers need to be proved in additional cohorts. Second, only a few preliminary studies have shown that the highest diagnostic accuracy would be achieved from the combination of advanced multiparameter MRI and PET imaging ( 9 , 12 , 34 , 36 , 64 ), and therefore future research should focus on the development and validation of such bimodal or multimodal diagnostic models ( 65 ). In addition, the kinetic parameters of dynamic PET imaging have demonstrated excellent performance in glioma grading ( 66 ) and prognosis evaluation ( 16 , 35 , 38 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…52 Intratumoral hypoxia is associated with resistance to treatment and entails radiation to hypoxic subregions of tumors. [ 18 F] fluoromisonidazole, a nitroimidazole derivative that images viable hypoxic cells, a biomarker of glioblastoma that correlates with prolonged overall survival 53 and distinguishes pseudoprogression from recurrence in patients with HGGs treated with pembrolizumab 54 [ 18 F]-GE-180 (a novel TSPO ligand), is an imaging biomarker of tumor heterogeneity with improved binding affinity and a high TBR in glioblastoma. TSPO-PET can differentiate potentially aggressive forms of gliomas, graded according to the World Health Organization (WHO) classification, with a positive rate on PET of 100% among the HGGs.…”
Section: Monitoring Treatment Response To Newer Drugs In Recurrent Hg...mentioning
confidence: 99%